2018
DOI: 10.1158/0008-5472.can-17-1631
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2-2as Suppression Contributes to the Pathogenesis of Sonic Hedgehog Medulloblastoma

Abstract: Aberrant Hedgehog signaling and excessive activation of the Gli family of transcriptional activators are key drivers of medulloblastoma (MB), the most common human pediatric brain malignancy. MB originates mainly from cerebellar granule neuron progenitors (CGNP), but the mechanisms underlying CGNP transformation remain largely obscure. In this study, we found that suppression of the noncoding RNA Nkx2-2as promoted Sonic Hedgehog (Shh)-potentiated MB development. Nkx2-2as functioned as a competing endogenous RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
0
28
0
2
Order By: Relevance
“…FOXD1 is associated with cell programming, especially in renal and kidney development [7][8][9][10]. Abnormal FOXD1 expression is involved in the progression of tumors [11] including breast cancer [12], colorectal cancer, melanoma, glioma [13], osteosarcoma, renal cell carcinoma, ovarian carcinoma, medulloblastoma [14], and lung cancer [15]. Recently, clinical mRNA microarray data identified FOXD1 as a factor associated with poor prognosis and that is required for lung cancer cell proliferation [15].…”
Section: Introductionmentioning
confidence: 99%
“…FOXD1 is associated with cell programming, especially in renal and kidney development [7][8][9][10]. Abnormal FOXD1 expression is involved in the progression of tumors [11] including breast cancer [12], colorectal cancer, melanoma, glioma [13], osteosarcoma, renal cell carcinoma, ovarian carcinoma, medulloblastoma [14], and lung cancer [15]. Recently, clinical mRNA microarray data identified FOXD1 as a factor associated with poor prognosis and that is required for lung cancer cell proliferation [15].…”
Section: Introductionmentioning
confidence: 99%
“…NKX2-2AS was shown in vitro to modulate SHH-potentiated MB development by acting as a miRNA sponge for miR-103 and miR-107, thereby depressing their tumor suppressive targets BTG2 and LATS1 and inhibiting proliferation and migration [42]. CDKN2B-AS1 (ANRIL) has been shown to promote proliferation in vitro studies by sponging miR-323 and activating BRI3 dependent p38-MAPK, AKT and WNT signaling [43], and in current analysis, it was found to be upregulated in group 4 patients compared to other MBs.…”
Section: Discussionmentioning
confidence: 99%
“…In MB, it was also observed that lncRNA Nkx2-2as depress tumor suppressing targets BTG2 and LATS1 in the SHH subgroup of MB by competing with miR-103 and miR-107 and impeding cell proliferation and migration [ 181 ]. Knockdown of oncogenic lnc-IRX3-80 (CRNDE) inhibited tumor growth, significantly reduced cell proliferation, and increased the level of apoptosis in MB cell lines [ 182 ].…”
Section: Diagnostic and Therapeutic Potential Of Ncrnasmentioning
confidence: 99%